Analysis of the variability in collected peanut (Arachis hypogaea L.) cultivars for the establishment of core collections - Fundora Mayor, Z.=700 1 Hernandez, M.; Lopez, R.; Fernandez, L.; Sanchez, A.; Lopez, J.; Ravelo, I.
(En, Es, Fr)
ilus., 25 ref.
Keywords: ARACHIS HYPOGAEA; CONSERVACION DEL GERMOPLASMA; VARIACION GENETICA; ITALIA